QI-pathological constitution is associated with mental fatigue in class among university students: a cross-sectional study - Xinzhu Wang; Xinyu He (BMC Psychology)
Abstract Background Mental fatigue in class is a common phenomenon among university students in China. However, there is limited research exploring the impact of QI-pathological constitution on mental fatigue in university students. Methods We employed a convenience sampling method to survey 588 students aged 17 to 24 from a western university in China in May 2024. The study measured QI-pathological constitution and mental fatigue among these students. Additionally, diet quality, physical exercise, sleep quality, and academic pressure were assessed as controlled variables. Descriptive statistics, Pearson correlation, and structural equation modeling were utilized to analyze these cross-sectional data. Results The results showed that university students experience low levels of mental fatigue in class (M = 2.41, SD = 0.75) and a slight QI-pathological constitution (M = 1.96, SD = 0.71 for QI stagnation and M = 2.41, SD = 0.91 for QI deficiency) on a 5-point Likert scale ranging from 1(never) to 5(often). Pearson correlation analysis revealed a weak positive association between QI-pathological constitution (r = 0.205, p < 0.01 for QI stagnation; and r = 0.256, p < 0.01 for QI deficiency) and mental fatigue in class. Controlling for diet quality, physical exercise, sleep quality, and academic pressure in the structural equation model showed that QI-pathological constitution has a significantly positive effect on mental fatigue in class (β = 0.228, p < 0.01). Conclusion The study identified a low level of mental fatigue in class and a slight presence of QI-pathological constitution among university students. The QI-pathological constitution has a significantly positive impact on the level of mental fatigue experienced by university students in the classroom.